The buffering-boosting hypothesis of the expression of general and personal belief in a just world - Alves, H. (2014)
Although past research on the expression of belief in a just world (BJW) identified such statements as judgment norms, it has not ascertained whether their social value holds when individuals refer to good and bad outcomes. We investigated whether this is the case - a more stringent test of the "BJW as judgment norms" view. Participants judged the targets on two dimensions of social value: social desirability and social utility. We hypothesized, and found, that high versus low BJW buffered the negativity of the associated negative dimension(s) of discourses and boosted the positivity of the associated positive dimension(s) of discourses. This buffering-boosting pattern is discussed as revealing the system justification functions of the expression of BJW.